Is Environmental Sanitation as A Trigger Factor Leading to Stunting? - Kustriyanti, Dwi; Hastuti, Witri; Boediarsih, Boediarsih; Kusyati, Eni; Pratiwi, Nanik (JENDELA NURSING JOURNAL, 2024)
Background: Stunting became a chronic malnutrition issue that illustrates a growth failure. The prevalence of stunting is around 31-35%, which Demak contributes to 6,82% of children under five with stunting.Purpose: The major aim of the study was to determine the relationship between environmental sanitation with stunting.Methods: The study design used a cross-sectional community-based survey. The population was 32 mothers with stunting children under five years, and there were 30 wholes who were eligible for inclusion criteria. Data were collected by proportional random sampling, and data analysis performed a descriptive analysis dan chi-square test.Results: Environmental sanitation contributes to stunting (p=0,002 < 0,005). This study found that environmental sanitation such as water and house characteristics, and domestic waste disposal have significant factors leading to stunting.Conclusion: Good water, sanitation, and hygiene practice are related to stunting. The mother and family needily to keep a healthy environment to prevent stunts.Â Â